Enveloping lie algebras of low dimensional leibniz algebras. - Amini, Massoud; Sattarovich, Rakhimov Isamiddin; Langari, Seyed Jalal (Scientific Research Publishing, 2011)
We calculate the enveloping Lie algebras of Leibniz algebras of dimensions two and three. We show how these Lie algebras could be used to distinguish non-isomorphic (nilpotent) Leibniz algebras of low dimension in some cases. These results could be used to associate geometric objects (loop spaces) to low dimensional Leibniz algebras.